Análise conformacional de polímeros - Miyahara, Diogo Keiji (Universidade Federal de São Carlos, 2025)
Quality assurance in polymeric materials is a fundamental aspect for excellence and competitiveness in modern industry. In this scenario, polymer characterization techniques such as Differential Scanning Calorimetry (DSC), Thermogravimetry (TGA), and Fourier-Transform Infrared Spectroscopy (FTIR) emerge as indispensable tools. The strategic and integrated application of these methodologies not only ensures product conformity but also drives innovation and operational efficiency. Quality control is extremely important in industrial production, and these techniques allow for rigorous monitoring from raw materials to the finished product. Deviations in thermal properties (DSC), composition (TGA), or chemical structure (FTIR) can indicate potential problems that, if undetected, would lead to failures in the final product. This early detection capability is crucial to avoid significant losses and ensure reliability. This work aims to demonstrate the relevance of data obtained by these techniques to identify the causes of non-conformities presented in a defective material, highlighting the differences between a compliant and a non-compliant sample, and the importance of these techniques in current times.
Conformational analysis of polymers
Keywords: Polymers; Material analysis; Characterization; Polímeros; Análise de materiais; Caracterização; CIENCIAS EXATAS E DA TERRA::QUIMICA